Evidence-based pharmacological treatment options for ADHD in children and adolescents - Mechler, Konstantin; Banaschewski, Tobias; Hohmann, Sarah; Häge, Alexander (The international journal of neuropsychopharmacology, 2022)
Attention-deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder characterized by inattention, hyperactivity, and impulsivity, causing functional impairment. Its prevalence lies at approximately 5% in children and adolescents and at approximately 2.5% in adults. The disorder follows a multifactorial etiology and shows a high heritability. Patients show a high interindividual and intraindividual variability of symptoms, with executive deficits in several cognitive domains. Overall, ADHD is associated with high rates of psychiatric comorbidities, and insufficient treatment is linked to adverse long-term outcomes. Current clinical guidelines recommend an individualized multimodal treatment approach including psychoeducation, pharmacological interventions, and non-pharmacological interventions. Available medications include stimulants (methylphenidate, amphetamines) and non-stimulants (atomoxetine, guanfacine, clonidine). While available pharmacological treatment options for ADHD show relatively large effect sizes (in short-term trials) and overall good tolerability, there is still a need for improvement of current pharmacotherapeutic strategies and for the development of novel medications. This review summarizes available pharmacological treatment options for ADHD in children and adolescents, identifies current issues in research and evidence gaps, and provides an overview of ongoing efforts to develop new medications for the treatment of ADHD in children and adolescents by means of a systematic cross-sectional analysis of the clinical trials registry www.clinicaltrials.gov.
Online verfügbar: 23. Juni 2021, Artikelversion: 3. Februar 2022
Gesehen am 14.05.2024